Disjointed War Military Operations in Kosovo, 1999 - Nardulli, Bruce (RAND Corporation, 2002)
An examination of the 1999 conflict in Kosovo, with afocus on joint military operations.The 1999 military operation against the Yugoslav Army in Kosovosuggests several areas in which Joint military operations weredeficient. This study examined all aspects of the Kosovo conflict,including its political and historical underpinnings, in an attempt tounderstand these deficiencies and to recommend improvements. Thisdocument--provided in both a classified and unclassified version--isbased on extensive original source documents and interviews with mostof the principal participants, and serves as the definitive Armyrecord on Kosovo. While the primary focus of the research was on U.S.Army involvement, it covered many other aspects of Operation AlliedForce. Topics included NATO objectives in Operation Allied Force, airand ground planning, evolution of the air operation and its effects onfielded Yugoslav forces, Task Force Hawk, and peace operations. The 1999 military operation in Kosovo suggests severalareas in which Joint military operations were deficient. This studyexamines all aspects of the Kosovo conflict, with a focus on U.S. Armyinvolvement, including its political and historical underpinnings, inan attempt to understand these deficiencies and to recommendimprovements.